The six month fix adventures in rescuing failing companies - Sutton, Gary. (New York J. Wiley, 2002)
If you're the CEO of a struggling business, let's hope we nevermeet. I'm Gary Sutton, a turnaround guy. When I arrive you leave.Results usually get better and fast."-from the Introduction to TheSix-Month Fix
Includes index.
Keywords: Corporate turnarounds